Assessment co-creation mediated by technology and its relation to university students’ agency and self-regulation: The professors’ perspective - Santana Martel, Jennifer Saray; Pérez Garcías, Adolfina (Portuguese Journal of Education, 2024)
Assessment co-creation is emerging with increasing frequency in co-designing learning practices in technology-enhanced learning environments in higher education. Thus, the objective of this study is to analyse whether these practices are related to students’ self-regulation and agency. Therefore, a qualitative multi-case study from a phenomenology perspective was conducted. To collect data, six professors were interviewed (four female and two males) following a semi-structured approach in order to gain their perceptions of their experiences in the assessment co-creation process and their views on the relationship of this process to students’ self-regulation and agency. To analyse the data, a deductive coding method was followed using the data analysis tool Atlas.ti. The findings show that from the professors’ points of view various relationships exist between the assessment co-creation mediated by technologies and students’ self-regulation and agency. Interviewees perceived that assessment co-creation activated both students’ agency and their self-regulation skills. From the results, it is suggested that assessment co-creation can enhance students’ self-regulation in all its phases but mainly in terms of forethought. Similarly, students’ agency seems to be boosted by the co-design process, highlighting the effect on the individual dimension. Accordingly, and related to the more developed areas of students’ self-regulation and agency, motivation seems to increase while co-creating.